In a Pinch: Mechanisms Behind Potential Biotic Resistance Toward Two Invasive Crayfish by Native African Freshwater Crabs - South, Josie; Madzivanzira, Takudzwa C.; Tshali, Ntombizanele; Measey, John; Weyl, Olaf L. F. (Frontiers in Ecology and Evolution, 2020)
It is essential to incorporate mechanisms of biotic resistance into predictions of ecological impact conferred by invasive species. Trophically and functionally analogous native species have high potential to confer biotic resistance or to be susceptible to competitive exclusion by the invading species. In species with dominance hierarchies and high aggression the role of weapons, such as chelae, is emphasised and selected for. Differences in traits such as crushing capacity can indicate prey handling capabilities, while correlations between closing force and morphology can be used to understand the role of signalling in agonistic contests. Closing force strength can be used to infer the outcomes of both direct (predation) and indirect (competition) trophic interactions. Southern Africa has been invaded by two freshwater crayfish species (Cherax quadricarinatus and Procambarus clarkii). Biotic resistance of freshwater crabs towards crayfish invasions varies between geographic location and co-evolutionary history, thus comparing invasion histories without incorporating geographic context can produce unequivocal conclusions. We compared the closing force and chelae morphology of both crayfish species with a native trophically analogous freshwater crab, Potamonautes perlatus. Closing force increased significantly with mass for all species. There was significant interaction between sex and species on closing force. Potamonautes perlatus females showed significantly stronger maximum chela closing force than male P. perlatus, both sexes of P. clarkii and female C. quadricarinatus. Contrastingly, male C. quadricarinatus had significantly higher closing forces than both sexes of P. clarkii and female C. quadricarinatus, however, there was no difference between female P. perlatus. Native P. perlatus has the capacity to hold a competitive mechanical advantage over both invaders, but this varies with sex. Chelae length was not a significant predictor for closing strength in any of the species, which may be related to dishonest signalling in decapod species. This makes it imperative to assess whether factors such as closing force actually translate to resource holding potential in a contest scenario. We thus provide evidence that African freshwater crabs may exhibit biotic resistance towards invasion and the first measurements for C. quadricarinatus closing force strength.